Use of a Serious Game to Teach Infectious Disease Management in Medical School: Effectiveness and Transfer to a Clinical Examination - Aster, Alexandra; Scheithauer, Simone; Middeke, Angélina Charline; Zegota, Simon; Clauberg, Sigrid; Artelt, Tanja; Schuelper, Nikolai; Raupach, Tobias (Frontiers in Medicine, 2022)
Purpose: Physicians of all specialties must be familiar with important principles of infectious diseases, but curricular time for this content is limited and clinical teaching requires considerable resources in terms of available patients and teachers. Serious games are scalable interventions that can help standardise teaching. This study assessed whether knowledge and skills acquired in a serious game translate to better performance in a clinical examination. Methods: Fifth-year undergraduate medical students (n = 100) at Goettingen Medical School were randomised to three groups receiving different levels of exposure to virtual patients presenting with signs and symptoms of either infective endocarditis or community-acquired pneumonia in a serious game simulating an accident and emergency department. Student performance was assessed based on game logfiles and an objective standardised clinical examination (OSCE). Results: Higher exposure to virtual patients in the serious game did not result in superior OSCE scores. However, there was good agreement between student performance in the OSCE and in game logfiles (r = 0.477, p = 0.005). An Item Response Theory analysis suggested that items from the serious game covered a wider range of ability, thus better differentiating between students within a given cohort. Conclusion: Repeated exposure to virtual patients with infectious diseases in a serious game did not directly impact on exam performance but game logfiles might be good and resource-sparing indicators of student ability. One advantage of using serious games in medical education is standardised content, a lower inhibition threshold to learn, and a need of less staff time compared to small-group clinical teaching.